2022
DOI: 10.1111/ddi.13538
|View full text |Cite
|
Sign up to set email alerts
|

Freshwater macroinvertebrate traits assessment as complementary to taxonomic information for mining impact detection in the northern Peruvian Andes

Abstract: Aim:We studied the distribution of freshwater macroinvertebrate taxa and traits to distinguish ecological gradients among the mining-controlled and natural headwaters, and rural and urban economic activity influences.Location: In 2016's dry season, macroinvertebrate samples were collected at 40 locations in the Mashcon watershed, northern Peruvian Andes. Six locations were in the headwaters directly influenced by mining, eight near-pristine tributary headwaters, 14 agricultural locations at midstream and 12 ur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 85 publications
0
4
0
Order By: Relevance
“…Moreover, a 2012 study in the Mashcon watershed found that human dietary intakes of arsenic, cadmium, and lead were higher closer to the mine than downstream [ 8 ]. Another study found excellent physicochemical water quality in the RG upstream section but also ecological impairment in contrast to the natural headwaters [ 10 ]. Today, the GORE, JUM, SENAMHI, and a rural interviewee acknowledge that freshwater management is a much more complex challenge beyond mining impacts.…”
Section: Freshwater Management In the Mashcon Watershed: Historical B...mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, a 2012 study in the Mashcon watershed found that human dietary intakes of arsenic, cadmium, and lead were higher closer to the mine than downstream [ 8 ]. Another study found excellent physicochemical water quality in the RG upstream section but also ecological impairment in contrast to the natural headwaters [ 10 ]. Today, the GORE, JUM, SENAMHI, and a rural interviewee acknowledge that freshwater management is a much more complex challenge beyond mining impacts.…”
Section: Freshwater Management In the Mashcon Watershed: Historical B...mentioning
confidence: 99%
“…In the northern Peruvian Andes, the Yanacocha mine (MYSRL) exploits gold and silver ores at the headwaters of four watersheds, wherein two (Mashcon and Chonta) are sub-basins of the Amazon and the other two (Rejo and Honda) drain into the Pacific Slope [ 6 ]. Assessments downstream of the mine have found both positive (e.g., landowners increased income) [ 7 ] and negative impacts (e.g., human intake of heavy metals, land use planning lobbying, freshwater ecological impairment, and decreased phreatic level) [ 6 , 8 , 9 , 10 ]. Studies with no focus on mining, yet located in the MYSRL influence area, have reported anthropogenic pressures from logging, farming, and water abstraction for drinking and irrigation.…”
Section: Introductionmentioning
confidence: 99%
“…Several papers in this special issue provide practical examples on the use of trait‐based approaches for impact, risk, and vulnerability assessment. In one example, Mercado‐Garcia et al (2022) assess the impact of mining in a watershed on the functional changes of freshwater macroinvertebrate assemblages in the northern Peruvian Andes. They find clear ecological impairment (less macroinvertebrate diversity and changing phenotypic trait composition) of parts of the watershed impacted by mining relative to those that are not.…”
Section: Section B: Impact Risk and Vulnerability Assessmentmentioning
confidence: 99%
“…Traits in tropical countries are understudied and therefore little is known about the responses of macroinvertebrate traits towards flow velocity, turbidity, and accumulated impacts of human activities in these regions [ 20 ]. These environmental variables are particularly important, as studies have indicated that flow velocity, sedimentation, and multiple stressors strongly affect macroinvertebrate traits [ 21 , 22 , 23 , 24 ]. Although a few studies investigated the effect of flow velocity and sedimentation on macroinvertebrate traits, most are implemented in temperate regions or mesocosms [ 21 , 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%